The Effect of CRM on the Level of Pharmacy Consumer Satisfaction - Agustini, Kamelia; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Maulana, Teguh Nurakmal (Budapest International Research and Critics University, 2021)
This study focuses on CRM, namely drug information services, to determine the level of satisfaction of BPJS Health patients with CRM drug information services and to determine the effect of CRM on BPJS Health patient satisfaction levels at the Bandung City Pharmacy. This research belongs to the type of quantitative descriptive research with a survey approach, namely the technique of gathering information by giving a list of questions (questionnaires) to the respondents. The population in this study were BPJS health patients who redeemed drugs at the Padjadjaran Health Pharmacy, Bandung City. The research sample is 377 respondents who have been determined based on the Slovin formula. Data collection in this study used a non-random technique (non-probability sampling) with an accidental sampling method. The results showed that CRM is a drug information service at the Padjadjaran Health Pharmacy, Bandung City in terms of the results of questionnaire observations that have been carried out regularly, the level of satisfaction of BPJS Health patients with CRM. An average of 1520, CRM drug information services on the satisfaction level of BPJS Health patients at the Padjadjaran Health Pharmacy Bandung has an effect, but is not significant based on the statistical correlation value of 42.6%.